Employability Skills in Technical Vocational Education and Training (TVET) - Nugraha, Hari Din; Kencanasari, R. A. Vesitara; Komari, Reni Nuril; Kasda, Kasda (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
Employability skills should be a necessity for every TVET graduate. The need for the employability skills is very important in order to prepare TVET graduates in entering the labor market. The purpose of this study is: (1) to verify indicators of employability skills needed by TVET graduates and, (2) to produce proposals for employability skills frameworks for TVET graduates. This article reviews various relevant literature in order to explore the needs of appropriate employability skills. The results of the literature review show the employabilty skills needed by TVET sorted according to rank, namely; Social Skills, Knowledge in the Field of Engineering, Communication Skills, Information and Technology Skills, Management Skills, Creative and Innovative, Problem Solving and Critical Thinking. The implications of this literature review provide information and recommend a set of frameworks for academics to improve the employability skills of TVET graduates.